Strategi Manajemen Branding Sekolah Berbasis Pesantren: Pendekatan Inovatif Untuk Meningkatkan Daya Saing Pendidikan - Nanda Pratama, Farandika; Nugroho, Puspo; Rifa Zakaria, Ahmad; Dani Rohmatulloh, Naufal; Rifatul Muna, Lia (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The purpose of this study is to determine the implementation of branding management strategies of SMP PMS Kendal, socialization management, and management of Islamic boarding school institutions. Competition between formal educational institutions triggers the enthusiasm of managers to always make improvements and increase quality as is done by this SMP to build a brand image in the community and alumni of the school. This study uses a type of field research (qualitative approach) with a phenomenological approach accompanied by interview, observation and documentation data collection techniques. Respondents involved in this study include internal school principals and a number of teachers. Data analysis used through the stages of data reduction, data presentation and verification. The results of this study reveal that SMP Pondok Modern Selamat Kendal has implemented a branding management strategy that highlights the uniqueness of Islamic boarding school-based schools with very different differentiation values ​​and is rarely owned by other school institutions in Central Java and this is part of the novelty of this research study. The role and contribution of alumni are very important in publication management accompanied by the use of brochures and social media as a means of publication and branding promotion so that there is optimization of media content, complete and modern infrastructure facilities so as to support academic, character, moral, spiritual and skills development programs for teachers and students with quality and competent HR management in the management of their school institutions. It is hoped that this research can fill the gap in previous research on the development of innovation in Islamic boarding school management, especially in the Central Java region and provide a positive contribution as a model for Islamic school branding management strategies for other institutions.